CONTRIBUTION OF TEACHER PERFORMANCE TO STUDENT LEARNING MOTIVATION AT SDIT DARUT TAUBAH PANCORAN, SOUTH JAKARTA - Taufik, Taufik (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study aims to identify the contribution of teacher performance to student learning motivation at SDIT Darut Taubah Pancoran, South Jakarta. Method: The research uses a descriptive qualitative approach, with data collection through interviews, observations, and document analysis. Data sources include the school principal, teachers, students, and relevant documents such as student data, attendance records, and assessments. Result: The results show that teacher performance in enhancing student learning motivation has not been optimized. This is due to a lack of lesson planning, less varied teaching methods, and inconsistent assessments. However, supportive factors such as the teacher's strong personality, care for students, and professional development activities play a role in boosting student motivation. In contrast, inhibiting factors include poor communication between the principal and teachers, inadequate teaching resources, and a less supportive family environment. Conclusion: This study reveals the crucial role of teachers in fostering student motivation, emphasizing the need for improvements in lesson planning, teaching implementation, and stronger support from all parties, including families and school management.